First‐in‐human, randomized dose‐escalation study of the safety, tolerability, pharmacokinetics, pharmacodynamics and immunogenicity of PF‐06480605 in healthy subjects - Banfield, Christopher; Rudin, Dan; Bhattacharya, Indranil; Goteti, Kosalaram; Li, Gang; Hassan‐Zahraee, Mina; Brown, Lisa S.; Hung, Kenneth E.; Pawlak, Sylvester; Lepsy, Christopher (British journal of clinical pharmacology, 2020)
Aims Human genetic, tissue expression, proteomics, transcriptomics and nonclinical studies implicate tumour necrosis factor α‐like ligand 1A (TL1A) as a novel target in inflammatory bowel disease (IBD). PF‐06480605, a fully human immunoglobulin G1 monoclonal antibody, targets TL1A. This first‐in‐human, Phase 1, dose‐escalation study assessed safety, tolerability, pharmacokinetics, pharmacodynamics and immunogenicity of intravenous (IV) and subcutaneous (SC) PF‐06480605 in healthy subjects (NCT01989143). Methods Ninety‐two subjects were randomized to single ascending doses (SAD), PF‐06480605 1 mg, 3 mg, 10 mg, 30 mg, 100 mg, 300 mg, 600 mg or 800 mg IV, or multiple ascending doses (MAD), PF‐06480605 3 × 500 mg IV, or 3 × 30 mg, 3 × 100 mg, or 3 × 300 mg SC every 2 weeks for three doses, or placebo. Safety, tolerability, pharmacokinetics, immunogenicity profiles and total TL1A, anti‐drug antibody (ADA) and neutralizing antibody (NAb) levels were assessed at pre‐determined times. Results PF‐06480605 SAD up to 800 mg IV and MAD up to 300 mg ×3 SC and 500 mg ×3 IV were well tolerated. Overall, there were 45 and 44 treatment‐emergent adverse events in SAD and MAD cohorts, respectively, and no deaths or serious adverse events. PF‐06480605 exposure generally increased dose‐dependently. ADA and NAb levels did not impact safety, pharmacokinetics, or pharmacodynamics at higher doses. Target engagement was demonstrated through dose‐dependent differences in serum total soluble TL1A concentrations for PF‐06480605 vs placebo cohorts. Conclusions PF‐06480605 was generally well tolerated, and binding of soluble TL1A was maintained throughout the dose interval, supporting further study of PF‐06480605 in patients with IBD and other inflammatory conditions.